The effects of aerator noise on the swimming, feeding, and growth of Micropterus salmoides - Zhang, Yadong; Shitu, Abubakar; Hang, Shengyu; Ye, Zhangying; Zhao, Hangfang; Xu, Wen; Zhao, Jian; Zhu, Songming (Frontiers in Marine Science, 2023)
Aquaculture systems, replete with equipment noise originating from aerators, pumps, feeders, and filtration systems, are known to exert substantial influence on fish behavior and growth. In this research, the focus was directed towards comprehending the impacts of aerator noise on the swimming, feeding, and growth progression of largemouth bass. In the course of a 50-day experimental period, the bass population was segmented into two groups: aerator noise (90.3dB re μPa RMS-1) and ambient noise (70.4dB re μPa RMS-1). The findings indicated discernible disparities in the swimming behavior and feeding between the two groups. Specifically, bass in the noise group maintained greater average angular distance and physical separation from their nearest counterparts than the bass in the ambient group, which were 43.61 ± 1.89° and 85.47 ± 1.72mm for the ambient group and 48.32 ± 0.49° and 97.01 ± 0.57mm for the noise group. Furthermore, the feeding kinetic energy was markedly lower in the noise group as compared to the ambient group. For the first time, the Shannon-Wiener diversity index was leveraged to gauge the diversity of fish swimming behavior, with the results signifying the diversity index of the noise group was 2.69 ± 0.07 higher than that of the ambient group, which was 2.51 ± 0.02. Lastly, the noise group demonstrated compromised growth performance, with a significantly lower average weight as opposed to the ambient group, along with marked variations in the specific growth rate. These findings offer a telling revelation about the profound impacts of aerator noise on the behavioral and growth of largemouth bass, thereby forming a valuable referential base for future research centered on the effects of noise pollution on aquatic organisms.